PENGARUH MODEL ACCELERATED LEARNING CYCLE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MATERI BILANGAN BULAT - Dwi Sucipto Mandala Putra; Sri Sugiyarti; Yudi Yunika Putra (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2018)
The research aims at knowing the influence of Accelerated Learning Cycle Model on Mathematic Problem Solving of Integers material. The method used in this research was quantitative approach with pre-experimental method. The research used One Group Pretest-Posttest Design. The research was conducted at Grade IV SDN 13 Sungaiselan, Central Bangka Regency. The techniques of data analysis were through the use of Lilliefors normality test and The Related hypothesis test. The result of the research was Accelerated Learning Cycle Model influenced Mathematic Problem Solving of Integers material.